Left bundle branch pacing in a 4-year-old patient with complete heart block after correction of transposition of the great arteries via a dual chamber pacing system: a case report - Omar Fakhreddine; Patrick Sarkis; Jamil Francis; Bernard Abi-Saleh (Frontiers in Cardiovascular Medicine)
Conduction system pacing is a recently developed pacing modality that serves as an alternative approach in maintaining or restoring physiological ventricular activity. Left bundle branch pacing (LBBP) has been rarely performed in children due to concerns regarding its safety and feasibility. Here, we report a case of successful LBBP in a 4-year-old patient with complete heart block following repair of transposition of the great arteries.